The association between the gut microbiota metabolite trimethylamine N-oxide and heart failure - Jarmukhanov, Zharkyn; Mukhanbetzhanov, Nurislam; Kozhakhmetov, Samat; Nurgaziyev, Madiyar; Sailybayeva, Aliya; Bekbossynova, Makhabbat; Kushugulova, Almagul (Frontiers in Microbiology, 2024)
The purpose of this systematic review is to develop the concept of the relationship of the gut microbiota metabolite, trimethylamine N-oxide and heart failure. Considering the critical impact that TMAO has on cardiovascular health, the results of our study show that high levels of TMAO are accompanied by atherosclerosis, endothelial dysfunction, and subsequent cardiovascular diseases and can further aggravate heart failure. Our research is a systematic search and meta-analysis of peer-reviewed published papers from 2013 to 2024 adult patients with heart failure and healthy controls. In summary, the current review compiles evidence of the relationship between TMAO level with several cardiovascular risk indicators such as LVEF and GFR, which further supports the role of TMAO as an important biomarker for HF assessment and management. The retrieved evidence implies that interventions aiming to alter gut microbiota and reduce TMAO could have the potential to help patients with HF.